INNOVATIVE MODELS OF EDUCATION AND TRAINING OF SKILLED PERSONNEL FOR HIGH TECH INDUSTRIES IN UKRAINE (Journal of Information Technologies in Education (ITE), 2013)
The problems of development of innovative learning environment of continuous education and training of skilled personnel for high-tech industry are described. Aspects of organization of ICT based learning environment of vocational and technical school on the basis of cloud computing and outsourcing are revealed. The three-stage conceptual model for perspective education and training of workers for high-tech industries is proposed. The model of cloud-based solution for design of learning environment for vocational education and training of skilled workers is introduced.
Keywords: e-learning environment; cloud computing; vocational education